Endoscopic management of 345 small rectal neuroendocrine tumours: A national study from the French group of endocrine tumours (GTE). Issue 8 (1st October 2019) - Fine, Caroline; Roquin, Guillaume; Terrebonne, Eric; Lecomte, Thierry; Coriat, Romain; Do Cao, Christine; de Mestier, Louis; Coffin, Elise; Cadiot, Guillaume; Nicolli, Patricia; Lepiliez, Vincent; Hautefeuille, Vincent; et al.
Abstract : Introduction: Small rectal neuroendocrine tumours are good candidates for endoscopic resection provided that complete pathological resection (R0) is obtained and their risk of metastatic progression is low. We conducted a large multicentre nationwide study to evaluate the outcomes of the management of non‐metastatic rectal neuroendocrine tumours ≤2 cm diagnosed endoscopically. Patients and methods: The medical records, the endoscopic and pathological findings of patients with non‐metastatic rectal neuroendocrine tumours ≤2 cm managed from January 2000–June 2018 in 16 French hospitals, were retrospectively analysed. The primary objective was to describe the proportion of R0 endoscopic resections. Results: A total of 329 patients with 345 rectal neuroendocrine tumours were included, 330 (96%) tumours were managed by local treatments: 287 by endoscopy only and 43 by endoscopy followed by transanal endoscopic microsurgery. The final endoscopic R0 rate was 134/345 (39%), which improved from the first endoscopy (54/225, 24%), to the second (60/100, 60%) and the third endoscopy (20/26, 77%). R0 was associated with endoscopic technique (90% for advanced techniques, 40% for mucosectomy and 17% for polypectomy), but not with tumour or patient characteristics. Twenty patients had metastatic disease, which was associated with tumour size ≥10 mm (odds ratio: 9.1, 95% confidence interval (3.5–23.5)), tumour grade G2–G3 (odds ratio: 4.2, (1.5–11.7)), the presence of muscular (odds ratio: ∞, (11.9–∞)) and lymphovascular invasion (odds ratio: 57.2, (5.6–578.9)). Conclusions: The resection of small rectal neuroendocrine tumours often requires multiple procedures. Training of endoscopists is necessary in order to better recognise these tumours and to perform the appropriate resection technique.